Does stroke volume limit exercise capacity in TGA patients after the arterial switch operation? - Renée S. Joosen; Michiel Voskuil; Wieke G. de Pater; Sebastiaan W.H. van Wijk; Dominika Suchá; Abraham van Wijk; Heleen B.van der Zwaan; Gregor J. Krings; Tim Takken; Johannes M.P.J. Breur (International Journal of Cardiology Congenital Heart Disease)
Background: Patients with transposition of the great arteries (TGA) experience reduced exercise capacity after the arterial switch operation (ASO), possibly due to limited stroke volume. This study evaluates the role of stroke volume in reduced exercise capacity in these patients. Methods: A retrospective analysis was conducted on TGA patients who underwent a transthoracic echocardiogram (TTE), cardiac magnetic resonance (CMR) and cardiopulmonary exercise test (CPET) within one year between September 2009 and February 2024 at the University Medical Center Utrecht. Excluding those with submaximal CPET results, the remaining patients were divided into <18 and ≥ 18 years old groups. Reduced exercise capacity was defined as a peak oxygen uptake (VO2peak) with a Z-score < -2. Left and right ventricular (LV and RV) data including volumes, function, strain and RV outflow tract obstructions were collected from TTE and CMR. Results: A total of 126 patients (72 % male, mean age 19 ± 8 years) were included. Left ventricular function, RV volumes, function and strain were relatively preserved on CMR. Reduced VO2peak was seen in 55 % of patients ≥18 years, significantly more than those <18 years (23 %, p < 0.001). Reduced VO2peak was independently associated with time since ASO, body mass index, peak heat rate (HRpeak), and O2pulse. VO2peak showed weak to moderate correlations with time after ASO (R = −0.295,p < 0.001), body mass index (R = −0.468,p < 0.001) and HRpeak (R = 0.270,p = 0.002) and a strong correlation with O2pulse (R = 0.621,p < 0.001). Conclusion: Exercise capacity in TGA patients after ASO might be limited by an impaired ability to increase stroke volume.